A reaction path for directly converting ethanol into p-xylene and a catalyst thereof

CN122974359APending Publication Date: 2026-10-27NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611151692.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]目前,乙醇转化制备对二甲苯技术尚未报道

Benefits of technology

现有技术通过甲醇芳构化和甲苯甲基化来制备对二甲苯,本发明对比现有技术主要有三方面的优势,使用可再生平台化合物乙醇作为原料;使用了脱铝ZnY/Si-Beta催化剂,以Si-Beta分子筛作为载体可以显著提高C-C偶联反应的速率,并通过Zn和Y物种之间的协同作用促进乙醇向丁二烯的定向转化;通过纳米片状ZnGa/ZSM-5催化剂,降低丁二烯在ZSM-5分子筛外部晶粒表面和外部孔表面上发生反应生成芳烃的可能性,促进丁二烯中间体在ZSM-5交叉孔隙通道中定向生成对二甲苯。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974359A_ABST
    Figure CN122974359A_ABST
Patent Text Reader

Abstract

The application discloses a reaction path for directly converting ethanol into p-xylene and a catalyst thereof, and belongs to the technical field of catalysts. Green ethanol is used as a raw material in the application, isolated Zn and Y species are effectively bridged on a dealuminated Si-Beta molecular sieve, and the synergistic effect between the Zn and Y species is further promoted, so that the directional conversion of ethanol into butadiene is significantly improved. Butadiene is more likely to generate para-substituted aromatic hydrocarbons in the cross-pore channels of nanosheet ZSM-5, and the byproduct olefins of the upper-layer catalyst can also generate aromatic hydrocarbons in an acid environment regulated by Zn and Ga species, so that the selectivity of p-xylene is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, and in particular relates to a reaction pathway for the direct conversion of ethanol to para-xylene and its catalyst. Background Technology

[0002] p-Xylene (PX) is the most valuable isomer of xylene, primarily used in the production of terephthalic acid and dimethyl terephthalate. Currently, PX is mainly derived from aromatics produced via traditional petroleum routes, such as naphtha catalytic reforming, xylene isomerization, toluene imbalance and alkylation transfer, crystallization, and adsorption separation—all energy-intensive processes. With the development of the polyester industry, the demand for PX is rapidly increasing, making the development of new synthetic routes to reduce dependence on petroleum crucial. Ethanol, as a renewable carbon source, is mainly derived from biomass fermentation; therefore, the direct conversion of ethanol to p-xylene is a very promising production process, which can not only alleviate dependence on fossil resources but also promote low-carbon energy conversion and green sustainable development.

[0003] Currently, there are no reports on the technology for converting ethanol to produce p-xylene. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a reaction pathway and catalyst for the direct conversion of ethanol to p-xylene. The bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 provided by this invention consists of an upper catalyst made of dealuminated Si-Beta molecular sieve, onto which Zn and Y are loaded using an impregnation method. The lower catalyst is a nano-ZSM-5 molecular sieve synthesized via a hydrothermal method, onto which Zn and Ga are then loaded using an impregnation method. This invention provides a novel pathway for the efficient conversion of ethanol to p-xylene using butadiene as an intermediate. The synergistic effect of Zn, Y, and Ga species effectively modulates the acidity of the catalyst, enabling the efficient conversion of ethanol to p-xylene using the ZnY / Si-Beta|ZnGa / ZSM-5 bilayer catalyst. The upper catalyst catalyzes the conversion of ethanol to butadiene, while the lower catalyst, through its synergistic effect, efficiently controls the selectivity of p-xylene during the catalytic process. Using the catalyst provided by this invention, p-xylene can be prepared directly from ethanol with high selectivity.

[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5, comprising an upper layer of dealufted ZnY / Si-Beta molecular sieve and a lower layer of nanosheet-like ZnGa / ZSM-5 molecular sieve, wherein the dealufted ZnY / Si-Beta molecular sieve and the nanosheet-like ZnGa / ZSM-5 molecular sieve are separated by quartz wool.

[0006] Furthermore, the mass ratio of the dealuded ZnY / Si-Beta molecular sieve to the nanosheet ZnGa / ZSM-5 molecular sieve is 1:1; the particle size of both the dealuded ZnY / Si-Beta molecular sieve and the nanosheet ZnGa / ZSM-5 molecular sieve is 20-40 mesh.

[0007] Secondly, the present invention provides a method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5, comprising the following steps: S1. Add the silicon source to an alkaline aqueous solution containing an aluminum source and a template agent, and stir to obtain a uniform sol; S2. The homogeneous sol is crystallized, centrifuged, washed, dried and calcined to obtain Beta molecular sieve; S3. The Beta molecular sieve is added to a concentrated nitric acid solution to carry out a dealumination reaction, and then calcined to obtain a dealumination Si-Beta molecular sieve; S4. The dealuminized Si-Beta molecular sieve is immersed in a mixed aqueous solution of soluble zinc salt and soluble yttrium salt, then removed, dried, and calcined to obtain a dealuminized ZnY / Si-Beta molecular sieve; S5. Add ethanol to an alkaline solution containing an aluminum source and a template agent, then add a silicon source and stir to obtain a uniform gel; S6. The uniform gel is crystallized, centrifuged, washed, dried and calcined to obtain nanosheet ZSM-5 molecular sieve; S7. The nanosheet ZSM-5 molecular sieve is added to ammonium nitrate solution to carry out ion exchange reaction, and then calcined to obtain nanosheet HZSM-5 molecular sieve. S8. The nanosheet-like HZSM-5 molecular sieve is immersed in a mixed aqueous solution of soluble zinc salt and soluble gallium salt, then removed and calcined to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve; S9. The dealuminated ZnY / Si-Beta molecular sieve and the nanosheet ZnGa / ZSM-5 molecular sieve are granulated and placed on both sides of quartz wool to obtain the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5.

[0008] Furthermore, the silicon source is selected from tetraethyl orthosilicate, fumed silica, or silica sol; and / or, the aluminum source is selected from aluminum chloride, aluminum nitrate, and sodium aluminate; and the template agent is selected from one of tetrapropylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium bromide.

[0009] Further, in step S1, the molar ratio of the aluminum source, template agent and silicon source is (0.1~2):(0.1~1):1.

[0010] Further, in step S2, the crystallization temperature is 100–180 °C and the time is 12–96 h; the drying temperature is 30–150 °C and the time is 6–24 h; the calcination temperature is 400–600 °C and the time is 5–12 h. In step S3, the concentration of the concentrated nitric acid solution is 5–20 mol / L; the mass ratio of the Beta molecular sieve to the concentrated nitric acid solution is 1:(10–30); the temperature of the dealumination reaction is 50–80℃, and the time is 2–8 h; the calcination temperature is 350–550℃, and the time is 4–12 h. In step S4, the zinc loading in the dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%; the calcination temperature is 350–550 °C, and the time is 4–12 h.

[0011] The soluble zinc salt is selected from zinc nitrate, zinc acetate, or zinc chloride; the soluble yttrium salt is selected from yttrium nitrate, yttrium acetate, or yttrium chloride.

[0012] The temperature and time used during calcination can affect whether the metal and the molecular sieve form a bond, and isolated metal oxides can reduce the catalytic performance of the catalyst.

[0013] Further, in step S5, the molar ratio of the aluminum source, template agent, ethanol and silicon source is (0.02~1.6):(0.2~1):(20~80):1.

[0014] Further, in step S6, the crystallization temperature is 100–180 °C and the time is 12–96 h; the drying temperature is 30–150 °C and the time is 5–24 h; the calcination temperature is 400–600 °C and the time is 5–12 h. In step S7, the concentration of the ammonium nitrate solution is 1–5 mol / L; the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:(10–40); the temperature of the ion exchange reaction is 50–80℃ and the time is 2–8 h; the calcination temperature is 350–550℃ and the time is 4–12 h.

[0015] In this invention, the reaction temperature during dealuminization significantly affects whether the molecular sieve can be completely dealuminized. When the temperature is too high, the nitric acid evaporates too quickly, failing to achieve complete dealuminization; when the temperature is too low, the reaction cannot proceed. The calcination time has a significant impact on whether the concentrated nitric acid is completely burned off, and the residue of concentrated nitric acid will greatly reduce the catalytic performance of the catalyst.

[0016] Further, in step S8, the zinc loading in the nanosheet ZnGa / ZSM-5 molecular sieve is 2 wt.%, and the gallium loading is 2 wt.%; the calcination temperature is 350–550 °C, and the time is 4–12 h.

[0017] The soluble zinc salt is selected from zinc nitrate, zinc acetate, or zinc chloride; the soluble gallium salt is selected from gallium nitrate, gallium acetate, or gallium chloride.

[0018] This invention first synthesizes Beta molecular sieves using a hydrothermal method, then performs dealumination with concentrated nitric acid solution, followed by impregnation loading of Zn and Y. The synergistic effect between Zn and Y species in this invention promotes the directional conversion of ethanol to butadiene. Nanoscale ZSM-5 molecular sieves are synthesized using a hydrothermal method, followed by impregnation loading of Zn and Ga. The synergistic effect of Zn and Ga species in this invention effectively controls the acidity of the catalyst, enabling the conversion of butadiene and other low-carbon olefins to p-xylene on nanosheet ZSM-5 molecular sieves.

[0019] Thirdly, the present invention provides a reaction pathway for the direct conversion of ethanol to p-xylene, comprising the following steps: passing diluted ethanol gas into the activated bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 for heating reaction; the diluted ethanol gas is passed in from the direction of the dealuminated ZnY / Si-Beta molecular sieve.

[0020] Further, the activation treatment is as follows: under a N2 atmosphere, at a pressure of 0.1 MPa and a flow rate of 10–60 mL / min, the temperature is increased to 300–500 °C at a heating rate of 2 °C / min, and then held at this temperature for 2–10 h; the volume ratio of the diluted ethanol gas to ethanol in the diluted ethanol gas is 1:(0.2–2); the diluted ethanol gas is selected from one of N2, Ar, and CO2; the heating reaction temperature is 350–400 °C, and the mass hourly space velocity (HHSV) is 0.5–2 h. -1 .

[0021] The bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 was loaded into a fixed-bed reactor and pretreated for activation before the reaction. After pretreatment and activation, diluted ethanol gas was introduced for the reaction. Ethanol underwent a five-step reaction on the dealuminated ZnY / Si-Beta molecular sieve to generate butadiene. The nanosheet ZnGa / ZSM-5 molecular sieve generated p-xylene through dehydrogenation and olefin aromatization. Due to the presence of the butadiene intermediate, the selectivity of p-xylene was greatly improved. The five-step reaction included: (1) ethanol dehydrogenation to generate acetaldehyde; (2) acetaldehyde undergoing aldol condensation to generate 3-hydroxybutyraldehyde; (3) 3-hydroxybutyraldehyde dehydrating to generate crotonaldehyde; (4) crotonaldehyde undergoing MPV reduction reaction with ethanol to generate crotonol; (5) crotonol dehydrating to generate butadiene.

[0022] Existing technologies typically prepare para-xylene through petroleum thermal cracking and toluene methylation. This invention offers three advantages over existing technologies: ① It uses renewable ethanol as a raw material; ② The dealuated Si-Beta molecular sieve effectively bridges isolated Zn and Y species, further promoting the synergistic effect between them, thus significantly improving the directional conversion of ethanol molecules to butadiene; ③ The acidity of the catalyst is controlled by Zn and Ga, while its nanosheet structure greatly enhances the stability of the ZSM-5 molecular sieve in the conversion of ethanol to PX.

[0023] In this invention, the upper catalyst, a dealuminated ZnY / Si-Beta molecular sieve, converts ethanol into butadiene, while the lower catalyst, a nanosheet-like ZnGa / ZSM-5 molecular sieve, uses butadiene and other olefins as raw materials to promote the formation of p-xylene through C-C coupling and aromatization. Using the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 provided by this invention, p-xylene can be prepared from ethanol. The bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 provided by this invention can effectively promote the synergistic effect of the active centers in dehydration, oligomerization, and aromatization reactions, and also binds C4 olefins, significantly improving the selectivity of p-xylene.

[0024] The principle of this invention is as follows: Aluminum atoms in the Beta molecular sieve framework are removed through post-treatment dealumination to form a hierarchical porous structure. This unique pore system not only improves the mass transfer efficiency between reactants and products but also inhibits the aggregation of different active sites in the catalyst, thereby increasing the butadiene yield. The active centers for the conversion of ZSM-5 molecular sieves to aromatics are mainly located on the external crystal surface, external pore surface, and pore channels. Benzene and toluene are mainly generated on the external crystal surface and external pore surface; in the cross-channels, ethanol can be directionally converted to p-xylene through shape-selective catalysis. Furthermore, by altering the structural morphology of the ZSM-5 molecular sieve, more accessible acidic sites in the cross-channels are exposed, improving the selectivity for p-xylene. The lower catalyst uses butadiene and other low-carbon olefins as raw materials. The aromatization of C4 and C2 olefins and the bonding of C4 with C4 olefins make p-xylene more likely to become the major product in xylene synthesis. This invention is the first to propose a new reaction pathway for the efficient conversion of ethanol to p-xylene using butadiene as an intermediate, providing a novel approach for the green synthesis of p-xylene.

[0025] The key technical advantages of this invention are: Zn species promote the interaction between Y species and silanol groups, forming more open Las active centers, while Y species inhibit the formation of stronger Las active sites between Zn species and silanol groups, thereby suppressing self-condensation and cross-condensation reactions and further improving the selectivity of butadiene. Due to the construction of nanosheets, not only is the mass transfer efficiency between raw material and product molecules increased, improving stability, but also more accessible acidic sites in the cross-channels are provided to enhance the selectivity of p-xylene. By controlling the acid-base properties of the catalyst through Zn-Ga bimetallic loading, Ga species can inhibit the interaction between Zn species and silanol groups to form strong Lewis groups, inhibiting toluene formation and allowing more olefins to be converted to xylene. Butadiene, as the main raw material of the lower catalyst, is more likely to generate p-xylene, increasing the p-xylene content in xylene. This invention simultaneously uses dealullated ZnY / Si-Beta and nanosheet-shaped ZnGa / ZSM-5 molecular sieves, using the upper catalyst to first convert ethanol to butadiene, and then to p-xylene through the lower catalyst.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects: Existing technologies prepare p-xylene through methanol aromatization and toluene methylation. This invention offers three main advantages over existing technologies: it uses renewable platform compound ethanol as a raw material; it employs a dealuminated ZnY / Si-Beta catalyst, using Si-Beta molecular sieves as a support to significantly increase the rate of the CC coupling reaction and promote the directional conversion of ethanol to butadiene through the synergistic effect between Zn and Y species; and it utilizes nanosheet-like ZnGa / ZSM-5 catalysts to reduce the likelihood of butadiene reacting on the outer crystal surface and pore surface of ZSM-5 molecular sieves to form aromatics, thus promoting the directional formation of p-xylene from butadiene intermediates within the cross-pore channels of ZSM-5.

[0027] This invention provides a bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, which uses green ethanol as a raw material. It effectively bridges isolated Zn and Y species on a dealulated Si-Beta molecular sieve, further promoting the synergistic effect between Zn and Y species, thereby significantly improving the directional conversion of ethanol to butadiene. Butadiene more readily forms para-substituted aromatics in the cross-channels of the nanosheet-like ZSM-5, and the byproduct olefins of the upper catalyst can also form aromatics under an acidic environment regulated by Zn and Ga species, thus improving the selectivity for p-xylene. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 The image shows the XRD pattern of the dealuminized ZnY / Si-Beta molecular sieve prepared by S1 in Example 1. Figure 2 The image shows the XRD pattern of the nanosheet ZnGa / ZSM-5 molecular sieve prepared by S2 in Example 1. Figure 3 This is a scanning electron microscope image of the nanosheet-like ZnGa / ZSM-5 molecular sieve prepared by S2 in Example 1; Figure 4 This is a transmission electron microscope (TEM) image of the nanosheet-like ZnGa / ZSM-5 molecular sieve prepared by S2 in Example 1. Detailed Implementation

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0032] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0033] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0034] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0035] The room temperature in this invention refers to 25±2℃.

[0036] All raw materials used in the embodiments and comparative examples of this invention were obtained through commercial purchase.

[0037] Example 1 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix NaAlO2, NaOH and H2O and stir, then add tetraethylammonium hydroxide and stir thoroughly to form a clear mixture; S1-2. After stirring the mixture obtained in step S1-1, add tetraethyl orthosilicate and stir to obtain a uniform sol. S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (140℃, 12h), followed by centrifugation, washing with deionized water, drying (80℃, 12h), and calcination (500℃, 5h) to obtain Beta molecular sieve. S1-4. The Beta molecular sieve obtained in step S1-3 is added to a 10 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:20), and the dealuminization reaction is carried out at 80 °C for 4 h. This is repeated 3 times. The product is then calcined at 550 °C for 6 h to obtain dealuminized Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc acetate and yttrium nitrate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 500℃ for 4 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of NaAlO2, NaOH, H2O, tetraethylammonium hydroxide and tetraethyl orthosilicate is 1:0.05:30:0.1:1.

[0038] S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix NaAlO2, NaOH and water and stir, then add tetrapropylammonium hydroxide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add tetraethyl orthosilicate, and stir thoroughly to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (140℃, 12h), followed by centrifugation, washing with deionized water, drying (80℃, 12h), and calcination (400℃, 5h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. The nanosheet ZSM-5 molecular sieve obtained in step S2-3 is placed in a 1 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:20. Ion exchange is performed at 70℃ for 4 h, and repeated 3 times. The product is then calcined (550℃, 6 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc acetate and gallium nitrate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 550℃ for 6 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of NaAlO2, NaOH, water, tetrapropylammonium hydroxide, ethanol, and tetraethyl orthosilicate is 1:0.05:60:0.25:30:1. S3. Assembly of dealuminized ZnY / Si-Beta molecular sieves and nanosheet ZnGa / ZSM-5 molecular sieves: The dealuated ZnY / Si-Beta molecular sieve prepared in step S1 and the nanosheet ZnGa / ZSM-5 molecular sieve prepared in step S2 were respectively placed in a tablet press to form flat blocks, and then passed through a sieve to obtain granular catalysts with a particle size of 20-40 mesh. 0.4g of dealuated ZnY / Si-Beta molecular sieve and 0.4g of nanosheet ZnGa / ZSM-5 molecular sieve were respectively loaded into a reaction tube, which was arranged from top to bottom as follows: quartz wool, quartz sand, quartz wool, dealuated ZnY / Si-Beta molecular sieve, quartz wool, nanosheet ZnGa / ZSM-5 molecular sieve and quartz wool, to prepare a bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5.

[0039] It should be noted that the present invention does not limit the order of S1 and S2.

[0040] The ZnY / Si-Beta molecular sieve prepared in S1 of Example 1 and the nanosheet-like ZnGa / ZSM-5 molecular sieve prepared in step S2 were characterized by X-ray diffraction, and the results are as follows: Figure 1 and Figure 2 As shown in the XRD pattern, the dealuded ZnY / Si-Beta molecular sieve and the nanosheet ZnGa / ZSM-5 molecular sieve exhibited obvious BEA and MFI topological characteristic diffraction peaks, respectively, indicating the successful preparation of two catalysts. The nanosheet ZnGa / ZSM-5 molecular sieve prepared in step S2 was characterized using scanning electron microscopy and transmission electron microscopy, and the results are as follows. Figure 3 and Figure 4 As shown in the SEM and TEM images, the structure and morphology of the nanosheet ZnGa / ZSM-5 molecular sieve prepared in step S2 are visible. The active sites are concentrated in the internal cross-channels. This morphology can provide more accessible active sites, and the shorter diffusion path can allow reactants and intermediates to diffuse out in a timely manner, thus promoting the reaction rate.

[0041] Example 2 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix AlCl3, NaOH and H2O and stir, then add tetraethylammonium hydroxide and stir thoroughly to form a clear mixture; S1-2. After stirring the mixture obtained in step S1-1, slowly add fumed silica and stir to obtain a uniform sol. S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (120℃, 24h), followed by centrifugation, washing with deionized water, drying (50℃, 18h), and calcination (400℃, 6h) to obtain Beta molecular sieve. S1-4. The Beta molecular sieve obtained in step S1-3 is added to a 5 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:10), and the dealuminization reaction is carried out at 60 °C for 6 h. This is repeated 3 times. The product is then calcined at 400 °C for 8 h to obtain dealuminized Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc nitrate and yttrium nitrate, ultrasonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 400℃ for 6 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of AlCl3, NaOH, H2O, tetraethylammonium hydroxide, and fumed silica is 0.1:0.05:20:0.2:1. S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix AlCl3, NaOH and H2O and stir, then add tetrapropylammonium bromide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add silica sol, and stir vigorously to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (120℃, 24h), followed by centrifugation, washing with deionized water, drying (50℃, 24h), and calcination (500℃, 8h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. Place the nanosheet ZSM-5 molecular sieve obtained in step S2-3 in a 3 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:30, and perform ion exchange at 50℃ for 2 h, repeating 3 times. The product obtained is then calcined (350℃, 4 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc acetate and gallium acetate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 350℃ for 4 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of AlCl3, NaOH, H2O, tetrapropylammonium bromide, ethanol, and silica sol is 0.02:0.1:50:0.5:60:1. S3. Assembly of dealuminized ZnY / Si-Beta molecular sieve and nanosheet ZnGa / ZSM-5 molecular sieve: Same as in Example 1.

[0042] Example 3 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix Al(NO3)3, NaOH and H2O and stir, then add tetraethylammonium hydroxide and stir thoroughly to form a clear mixture; S1-2. After stirring the mixture obtained in step S1-1, slowly add the silica sol and stir to obtain a uniform sol. S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (160℃, 48h), followed by centrifugation, washing with deionized water, drying (100℃, 6h), and calcination (550℃, 8h) to obtain Beta molecular sieve. S1-4. The Beta molecular sieve obtained in step S1-3 is added to a 15 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:15), and the dealuminization reaction is carried out at 70 °C for 8 h. This is repeated 3 times. The product is then calcined at 500 °C for 10 h to obtain dealuminized Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc chloride and yttrium nitrate, ultrasonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 350℃ for 8 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of Al(NO3)3, NaOH, H2O, tetraethylammonium hydroxide and silica sol is 0.2:0.05:40:0.4:1.

[0043] S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix Al(NO3)3, NaOH and H2O and stir, then add tetrapropylammonium hydroxide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add fumed silica, and stir thoroughly to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (160℃, 48h), followed by centrifugation, washing with deionized water, drying (30℃, 6h), and calcination (450℃, 10h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. The nanosheet ZSM-5 molecular sieve obtained in step S2-3 is placed in a 5 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:40. Ion exchange is performed at 80℃ for 8 h, and repeated 3 times. The product is then calcined (550℃, 12 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc acetate and gallium chloride, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 400℃ for 8 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of Al(NO3)3, NaOH, H2O, tetrapropylammonium hydroxide, ethanol and fumed silica is 0.4:0.05:80:0.3:20:1.

[0044] S3. Assembly of dealuminized ZnY / Si-Beta molecular sieve and nanosheet ZnGa / ZSM-5 molecular sieve: Same as in Example 1.

[0045] Example 4 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix AlCl3, NaOH, and H2O and stir. Then add tetraethylammonium hydroxide and stir thoroughly to form a clear mixture. S1-2. After stirring the mixture obtained in step S1-1, slowly add tetraethyl orthosilicate and stir to obtain a uniform sol. S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (180℃, 96h), followed by centrifugation, washing with deionized water, drying (120℃, 12h), and calcination (450℃, 5h) to obtain Beta molecular sieve. S1-4. Add the Beta molecular sieve obtained in step S1-3 to a 20 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:30), and carry out a dealumination reaction at 50℃ for 2 hours. Repeat the reaction 3 times. The product is then calcined at 500℃ for 4 hours to obtain dealuded Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc nitrate and yttrium acetate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 450℃ for 10 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of AlCl3, NaOH, H2O, tetraethylammonium hydroxide, and tetraethyl orthosilicate is 0.6:0.05:50:0.6:1. S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix NaAlO2, NaOH and H2O and stir, then add tetrapropylammonium bromide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add silica sol, and stir thoroughly to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (180℃, 12h), followed by centrifugation, washing with deionized water, drying (30℃, 8h), and calcination (600℃, 12h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. The nanosheet ZSM-5 molecular sieve obtained in step S2-3 is placed in a 2 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:10. Ion exchange is performed at 60℃ for 6 h, and repeated 3 times. The product is then calcined (400℃, 8 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc chloride and gallium nitrate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 450℃ for 10 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of NaAlO2, NaOH, H2O, tetrapropylammonium bromide, ethanol, and silica sol is 1.4:0.05:40:0.7:50:1. S3. Assembly of dealuminized ZnY / Si-Beta molecular sieve and nanosheet ZnGa / ZSM-5 molecular sieve: Same as in Example 1.

[0046] Example 5 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix Al(NO3)3, NaOH and H2O and stir, then add tetrapropylammonium hydroxide and stir thoroughly to form a clear mixture; S1-2. After stirring the mixture obtained in step S1-1, slowly add fumed silica and stir to obtain a uniform sol. S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (100℃, 72h), followed by centrifugation, washing with deionized water, drying (150℃, 24h), and calcination (600℃, 10h) to obtain Beta molecular sieve. S1-4. The Beta molecular sieve obtained in step S1-3 is added to a 10 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:15), and the dealuminization reaction is carried out at 60℃ for 8 hours. This is repeated 3 times. The product is then calcined at 350℃ for 12 hours to obtain dealuminized Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc chloride and yttrium acetate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 550℃ for 12 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of Al(NO3)3, NaOH, H2O, tetrapropylammonium hydroxide, and fumed silica is 1.6:0.05:60:0.2:1. S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix AlCl3, NaOH and H2O and stir, then add tetraethylammonium hydroxide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add tetraethyl orthosilicate, and stir thoroughly to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (100℃, 96h), followed by centrifugation, washing with deionized water, drying (120℃, 20h), and calcination (400℃, 5h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. The nanosheet ZSM-5 molecular sieve obtained in step S2-3 is placed in a 4 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:30. Ion exchange is performed at 80℃ for 2 h, and repeated 3 times. The product is then calcined (450℃, 10 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc nitrate and gallium chloride, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 500℃ for 12 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of AlCl3, NaOH, H2O, tetraethylammonium hydroxide, ethanol, and tetraethyl orthosilicate is 1.6:0.05:30:0.9:40:1. S3. Assembly of dealuminized ZnY / Si-Beta molecular sieve and nanosheet ZnGa / ZSM-5 molecular sieve: Same as in Example 1.

[0047] Example 6 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix NaAlO2, NaOH and H2O and stir, then add tetrapropylammonium bromide and stir thoroughly to form a clear mixture; S1-2. After stirring the mixture obtained in step S1-1, slowly add silica sol (40 wt.%) and stir to obtain a uniform sol; S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (110℃, 36h), followed by centrifugation, washing with deionized water, drying (130℃, 8h), and calcination (550℃, 12h) to obtain Beta molecular sieve. S1-4. The Beta molecular sieve obtained in step S1-3 is added to an 8 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:12), and the dealuminization reaction is carried out at 55℃ for 5 hours. This process is repeated 3 times. The product is then calcined at 400℃ for 4 hours to obtain a dealuminized Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc acetate and yttrium chloride, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 350℃ for 6 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of NaAlO2, NaOH, H2O, tetrapropylammonium bromide, and silica sol is 1.2:0.05:30:1:1. S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix Al(NO3)3, NaOH and H2O and stir, then add tetraethylammonium hydroxide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add fumed silica, and stir thoroughly to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (160℃, 18h), followed by centrifugation, washing with deionized water, drying (150℃, 5h), and calcination (550℃, 10h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. Place the nanosheet ZSM-5 molecular sieve obtained in step S2-3 in a 1 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:40, and perform ion exchange at 60℃ for 5 h, repeating 3 times. The product obtained is then calcined (500℃, 9 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc nitrate and gallium acetate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 500℃ for 4 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of Al(NO3)3, NaOH, H2O, tetraethylammonium hydroxide, ethanol, and fumed silica is 0.1:0.05:100:0.2:80:1. S3. Assembly of dealuminized ZnY / Si-Beta molecular sieve and nanosheet ZnGa / ZSM-5 molecular sieve: Same as in Example 1.

[0048] Example 7 A bilayer catalyst, ZnY / Si-Beta|ZnGa / ZSM-5, is prepared by the following method: S1. Preparation of dealuminized ZnY / Si-Beta molecular sieves: S1-1. Mix NaAlO2, NaOH and H2O and stir, then add tetrapropylammonium hydroxide and stir thoroughly to form a clear mixture; S1-2. After stirring the mixture obtained in step S1-1, slowly add fumed silica and stir to obtain a uniform sol. S1-3. The uniform sol obtained in step S1-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (170℃, 24h), followed by centrifugation, washing with deionized water, drying (30℃, 12h), and calcination (600℃, 8h) to obtain Beta molecular sieve. S1-4. The Beta molecular sieve obtained in step S1-3 is added to a 16 mol / L concentrated nitric acid solution (the mass ratio of Beta molecular sieve to concentrated nitric acid solution is 1:18), and the dealuminization reaction is carried out at 60℃ for 7 h. This is repeated 3 times. The product is then calcined at 500℃ for 8 h to obtain dealuminized Si-Beta molecular sieve. S1-5. The dealuminized Si-Beta molecular sieve obtained in step S1-4 is immersed in a mixed aqueous solution of zinc chloride and yttrium chloride, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, and calcined in a muffle furnace at 400℃ for 8 h to obtain a dealuminized ZnY / Si-Beta molecular sieve. The zinc loading in the obtained dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%. The molar ratio of NaAlO2, NaOH, H2O, tetrapropylammonium hydroxide and fumed silica is 2:0.05:60:1:1. S2. Preparation of nanosheet-like ZnGa / ZSM-5 molecular sieves: S2-1. Mix Al(NO3)3, NaOH and H2O and stir, then add tetrapropylammonium hydroxide and stir thoroughly to form a clear mixture; S2-2. Add ethanol to the mixture obtained in step S2-1, then add tetraethyl orthosilicate, and stir thoroughly to obtain a uniform gel; S2-3. The uniform gel obtained in step S2-2 is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner for crystallization (110℃, 20h), followed by centrifugation, washing with deionized water, drying (130℃, 12h), and calcination (500℃, 10h) to obtain nanosheet ZSM-5 molecular sieve. S2-4. The nanosheet ZSM-5 molecular sieve obtained in step S2-3 is placed in a 1 mol / L ammonium nitrate solution, wherein the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:30. Ion exchange is performed at 50℃ for 4 h, and repeated 3 times. The product is then calcined (450℃, 11 h) to obtain nanosheet HZSM-5 molecular sieve. S2-5. The nanosheet-like HZSM-5 molecular sieve obtained in step S2-4 is immersed in a mixed aqueous solution of zinc chloride and gallium acetate, sonicated in a water bath ultrasonicator for 30 min, then dried at 80℃ for 6 h, ground into powder, placed in a muffle furnace, and calcined at 380℃ for 6 h to obtain nanosheet-like ZnGa / ZSM-5 molecular sieve. The zinc loading and gallium loading in the obtained nanosheet-like ZnGa / ZSM-5 molecular sieve are 2 wt.% and 2 wt.% respectively. The molar ratio of Al(NO3)3, NaOH, H2O, tetrapropylammonium hydroxide, ethanol and tetraethyl orthosilicate is 0.08:0.05:70:1:70:1. S3. Assembly of dealuminized ZnY / Si-Beta molecular sieve and nanosheet ZnGa / ZSM-5 molecular sieve: Same as in Example 1.

[0049] The reaction tubes filled with the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 in step S3 of Examples 1-7 were respectively loaded into a micro atmospheric pressure fixed-bed reactor to evaluate the bilayer catalyst. The test method is as follows: The bilayer catalyst was first pretreated and activated under the following conditions: under N2 atmosphere, pressure of 0.1 MPa, flow rate of 60 mL / min, temperature increased to 400℃ at a rate of 2℃ / min, and held at this temperature for 2 h. After activation, diluted ethanol was introduced to evaluate the catalytic performance. The reaction conditions were: N2 to ethanol volume ratio of 1:0.5, reaction temperature of 400℃, and space velocity (WHSV) of 0.6 h⁻¹. -1 The reaction products were analyzed online in a GC (gas chromatograph) equipped with an FID (flame ionization detector). The ethanol conversion and reaction product selectivity were calculated using the C-based normalization method, and the results are shown in Table 1.

[0050] Table 1 Catalytic performance of different catalysts in Examples 1-7 Comparative Example 1 The catalytic performance of the dealuminized ZnY / Si-Beta molecular sieve prepared in step S1 of Example 1 was examined using the same testing method as in Example 1, and the results are shown in Table 2.

[0051] Comparative Example 2 The catalytic performance of the nanosheet ZnGa / ZSM-5 molecular sieve prepared in S2 of Example 1 was examined using the same test method as in Example 1, and the results are shown in Table 2.

[0052] Comparative Example 3 Same as Example 1, except that 0.4g of dealuated ZnY / Si-Beta molecular sieve with a particle size of 20~40 mesh and 0.4g of nanosheet ZnGa / ZSM-5 molecular sieve in step S3 were mixed and the catalytic performance was examined according to the same test method as in Example 1. The results are shown in Table 2.

[0053] Comparative Example 4 Similar to Example 1, except that in steps S1-5, yttrium nitrate was replaced with zirconium nitrate in equimolar amounts to prepare dealullated ZnZr / Si-Beta molecular sieves. The performance of the bilayer catalyst prepared in this comparative example was measured using the same method as in Example 1, and the results are shown in Table 2.

[0054] Comparative Example 5 Same as Example 1, except that gallium nitrate in steps S2-5 was replaced with copper nitrate in equal molar amounts to obtain nanosheet ZnCu / ZSM-5 molecular sieve; the performance of the bilayer catalyst prepared in this comparative example was measured using the same method as in Example 1, and the results are shown in Table 2.

[0055] Table 2 Catalytic performance of different catalysts in Comparative Examples 1-5 As can be seen from Table 2, the butadiene selectivity in Comparative Example 1 is relatively high. Compared with the examples, it can be proved that the upper catalyst (dealuminized ZnY / Si-Beta molecular sieve) converts most of the ethanol into butadiene without generating p-xylene. This result better illustrates that the present invention provides a new system for the synthesis of p-xylene by generating p-xylene using butadiene as an intermediate.

[0056] In Comparative Example 2, toluene showed the highest selectivity among the aromatic products, proving that ethanol is converted into toluene-based aromatics via nanosheet ZnGa / ZSM-5 molecular sieves. Combined with the analysis in Table 1, it can be found that the bilayer catalyst provided by this invention can achieve higher selectivity for p-xylene, and the aromatization of butadiene as an intermediate improves the selectivity of p-xylene in aromatics.

[0057] In Comparative Example 3, the main product was ethylene, and the selectivity for p-xylene was significantly reduced. This is because the reaction of ethanol to p-xylene, with butadiene as an intermediate, is a very complex multi-step reaction. Doping the dealuminated ZnY / Si-Beta molecular sieve and the nanosheet ZnGa / ZSM-5 molecular sieve together disrupted the original reaction pathway, so the expected selectivity for p-xylene was not achieved.

[0058] In Comparative Example 4, the selectivity for p-xylene was lower than that in Example 1. This was because the butadiene generated by the upper catalyst (dealuminized ZnY / Si-Beta molecular sieve) was insufficient, resulting in the bilayer catalyst not achieving the expected effect.

[0059] In Comparative Example 5, the selectivity of p-xylene was even lower than that of the single catalyst. At the same time, a small portion of butadiene remained unconverted. This is because the large amount of butadiene produced by the upper catalyst (dealuminized ZnY / Si-Beta molecular sieve) was mostly converted into other byproducts by the lower catalyst (nanofabricated ZnGa / ZSM-5 molecular sieve), resulting in a decrease in the selectivity of p-xylene.

[0060] By studying the catalytic performance of single catalysts (dealuminated ZnY / Si-Beta molecular sieve, nanosheet ZnGa / ZSM-5 molecular sieve, and a mixture of the two catalysts), it was found that the dealuminated ZnY / Si-Beta catalyst achieved a butadiene selectivity of 61.1%, but no para-xylene was formed; the nanosheet ZnGa / ZSM-5 catalyst achieved a para-xylene selectivity of 18.5% and a butadiene selectivity of 3.9%. Combined with the data in Table 1, it can be seen that the bilayer catalyst provided by this invention achieves para-xylene selectivity that is unmatched by a single catalyst, and by tandem with the two catalysts, a new pathway for the efficient conversion of ethanol to para-xylene has been realized. Comparison Example 3, with the data in Table 1, shows that the mixture of the two catalysts does not achieve the catalytic performance of the single nanosheet ZnGa / ZSM-5 catalyst. This is because the butadiene generated by the dealuminated ZnY / Si-Beta catalyst can be almost completely converted in the nanosheet ZnGa / ZSM-5 catalyst, and due to the C4+C4 bonding, para-xylene is formed more effectively.

[0061] Comparative Examples 4 and 5, by changing the supported metal on the bilayer catalysts, showed significant fluctuations in the selectivity for p-xylene. Combined with the data in Table 1, this demonstrates the importance of ZnY and ZnGa in the bilayer catalysts constructed from dealuded ZnY / Si-Beta and nanosheet ZnGa / ZSM-5 in the conversion of ethanol to p-xylene.

[0062] Combining Tables 1 and 2, the dealuminated ZnY / Si-Beta catalyst catalyzes the conversion of ethanol to butadiene. The selectivity of p-xylene in aromatic hydrocarbons is effectively controlled by the tandem nanosheet ZnGa / ZSM-5 catalyst, realizing the development of a new pathway for the efficient conversion of ethanol to p-xylene using butadiene as an intermediate.

[0063] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5, characterized in that, It includes an upper layer of dealuminized ZnY / Si-Beta molecular sieve and a lower layer of nanosheet ZnGa / ZSM-5 molecular sieve, which are separated by quartz wool.

2. The bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 according to claim 1, characterized in that, The mass ratio of the dealuded ZnY / Si-Beta molecular sieve to the nanosheet ZnGa / ZSM-5 molecular sieve is 1:1; the particle size of both the dealuded ZnY / Si-Beta molecular sieve and the nanosheet ZnGa / ZSM-5 molecular sieve is 20-40 mesh.

3. A method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 as described in claim 1 or 2, characterized in that, Includes the following steps: S1. Add the silicon source to an alkaline aqueous solution containing an aluminum source and a template agent, and stir to obtain a uniform sol; S2. The homogeneous sol is crystallized, centrifuged, washed, dried and calcined to obtain Beta molecular sieve; S3. The Beta molecular sieve is added to a concentrated nitric acid solution to carry out a dealumination reaction, and then calcined to obtain a dealumination Si-Beta molecular sieve; S4. The dealuminized Si-Beta molecular sieve is immersed in a mixed aqueous solution of soluble zinc salt and soluble yttrium salt, then removed, dried, and calcined to obtain a dealuminized ZnY / Si-Beta molecular sieve; S5. Add ethanol to an alkaline solution containing an aluminum source and a template agent, then add a silicon source and stir to obtain a uniform gel; S6. The uniform gel is crystallized, centrifuged, washed, dried and calcined to obtain nanosheet ZSM-5 molecular sieve; S7. The nanosheet ZSM-5 molecular sieve is added to ammonium nitrate solution to carry out ion exchange reaction, and then calcined to obtain nanosheet HZSM-5 molecular sieve. S8. The nanosheet-shaped HZSM-5 molecular sieve is immersed in a mixed aqueous solution of soluble zinc salt and soluble gallium salt, then removed and calcined to obtain nanosheet-shaped ZnGa / ZSM-5 molecular sieve; S9. After granulating the dealuded ZnY / Si-Beta molecular sieve and the nanosheet ZnGa / ZSM-5 molecular sieve, they are placed on both sides of quartz wool to obtain the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5.

4. The method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 according to claim 3, characterized in that, The silicon source is selected from tetraethyl orthosilicate, fumed silica, or silica sol; and / or, the aluminum source is selected from aluminum chloride, aluminum nitrate, and sodium aluminate; and / or, the template agent is selected from one of tetrapropylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium bromide.

5. The method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 according to claim 3, characterized in that, In step S1, the molar ratio of the aluminum source, template agent and silicon source is (0.1~2):(0.1~1):

1.

6. The method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 according to claim 3, characterized in that, In step S2, the crystallization temperature is 100–180°C and the time is 12–96 h; the drying temperature is 30–150°C and the time is 6–24 h; the calcination temperature is 400–600°C and the time is 5–12 h. In step S3, the concentration of the concentrated nitric acid solution is 5–20 mol / L; the mass ratio of the Beta molecular sieve to the concentrated nitric acid solution is 1:(10–30); the temperature of the dealumination reaction is 50–80°C, and the time is 2–8 h; the calcination temperature is 350–550°C, and the time is 4–12 h. In step S4, the zinc loading in the dealuminized ZnY / Si-Beta molecular sieve is 4 wt.%, and the yttrium loading is 7 wt.%; the calcination temperature is 350–550 °C, and the time is 4–12 h.

7. The method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 according to claim 3, characterized in that, In step S5, the molar ratio of the aluminum source, template agent, ethanol and silicon source is (0.02~1.6):(0.2~1):(20~80):

1.

8. The method for preparing the bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 according to claim 3, characterized in that, In step S6, the crystallization temperature is 100–180 °C and the time is 12–96 h; the drying temperature is 30–150 °C and the time is 5–24 h; the calcination temperature is 400–600 °C and the time is 5–12 h. In step S7, the concentration of the ammonium nitrate solution is 1–5 mol / L; the mass ratio of the nanosheet ZSM-5 molecular sieve to the ammonium nitrate solution is 1:(10–40); the temperature of the ion exchange reaction is 50–80°C, and the time is 2–8 h; the calcination temperature is 350–550°C, and the time is 4–12 h. In step S8, the zinc loading in the nanosheet ZnGa / ZSM-5 molecular sieve is 2 wt.%, and the gallium loading is 2 wt.%; the calcination temperature is 350–550 °C, and the time is 4–12 h.

9. A reaction pathway for the direct conversion of ethanol to p-xylene, characterized in that, Includes the following steps: Diluted ethanol gas is introduced into the activated bilayer catalyst ZnY / Si-Beta|ZnGa / ZSM-5 for heating reaction; the diluted ethanol gas is introduced from the direction of the dealuminated ZnY / Si-Beta molecular sieve.

10. The reaction pathway for the direct conversion of ethanol to p-xylene according to claim 9, characterized in that, The activation treatment is as follows: under N2 atmosphere, at a pressure of 0.1 MPa and a flow rate of 10–60 mL / min, the temperature is increased to 300–500℃ at a heating rate of 2℃ / min, and then kept at the temperature for 2–10 h. The volume ratio of the gas used to dilute the ethanol to the ethanol in the diluted ethanol gas is 1:(0.2~2); the gas used to dilute the ethanol is selected from one of N2, Ar and CO2; The heating reaction is carried out at a temperature of 350–400°C and a mass hourly space velocity (HHSV) of 0.5–2 h. -1 .